Turnover-dominated beta diversity among three Vietnamese natural broadleaf evergreen forest regions - NGUYEN TOAN THANG; NGUYEN TRONG MINH; TRINH NGOC BON; DAO TRUNG DUC; LUONG THE DUNG; DOAN THUY DUONG; VU TIEN LAM; TRUONG TRONG KHOI; TRAN HOANG QUY; NGUYEN VAN TUAN; PHAM TIEN DUNG; NGUYEN HUY HOANG; NGUYEN TRONG TAI; PHUNG VAN TINH; TRAN VAN DO (Society for Indonesian Biodiversity, 2026)
Abstract. Thang NT, Minh NT, Bon TN, Duc DT, Dung LT, Duong DT, Lam VT, Khoi TT, Quy TH, Tuan NV, Dung PT, Hoang NH, Tai NT, Tinh PV, Do TV. 2026. Turnover-dominated beta diversity among three Vietnamese natural broadleaf evergreen forest regions. Biodiversitas 27 (8): d270807. https://doi.org/10.13057/biodiv/d270807. Beta diversity, the variation in species composition among communities, is a fundamental axis of tropical biodiversity that determines how effectively a network of forest patches conserves regional species richness. Yet quantitative, multivariate assessments of beta diversity remain sparse for the forests of mainland Southeast Asia, and the contributions of turnover versus nestedness to inter-regional compositional differences are essentially unknown for Vietnam. We addressed these gaps using an extensive dataset of 8,474 trees belonging to 457 species from 75 families, enumerated across 59 permanent sample plots distributed among three regions of Vietnam: the Northeast (NE: 18 plots), the North Central coast (NC: 16 plots), and the Central Highlands (CH: 25 plots). Pairwise Sørensen dissimilarity ranged from 0.47 (NC-CH) to 0.54 (NE-NC, NE-CH). Turnover dominated beta diversity in all regional pairs (71-99% of total βsor). Permutational multivariate analysis of variance (PERMANOVA) on Bray-Curtis dissimilarity computed from plot-by-species abundance matrices confirmed highly significant compositional differences among all three regions (pseudo-F: 3.88, R²: 0.122, p: 0.0001) and between all pairwise combinations (all raw p≤0.0003, below the Bonferroni threshold of α: 0.0167). Principal coordinates analysis (PCoA) explained 15.6% of compositional variance on the first two axes, with regional centroids separated. The three regions share just 76 ubiquitous species (16.6% of total richness), whereas 63, 49, and 135 species are exclusive to NE, NC, and CH, respectively. These patterns are consistent with three floristically distinct regional assemblages shaped by the Truong Son (Annamite) range and a latitudinal gradient from subtropical to tropical climate. Conservation of Vietnam's sampled forest flora requires representation across all three regions; a Northeast-only or North Central-only strategy would omit approximately 54% of pooled sampled richness, while a Central Highlands-only strategy would omit approximately 29%.